Uruk Pottery from the Dokan and Shahr azur Districts and the Distribution of Ninevite V Pottery as Revealed by Field Survey Work in Iraq - Abu es-Soof, Behnam
ersch. 1966; 42-44: Aufzählung von 87 sites.